The Effect of Stimulation, Detection, and Early Intervention Development Training Based on Group Dynamics on Motivation and Skill among Cadre - Sari, Tria Puspita; Haryanti, Rusiana Sri (Journal of Maternal and Child Health, 2019)
Background: Early childhood development monitoring by cadre was an effort to detect delayed development among children. Knowledge of child growth and development was highlighted as important for all cadres. Based on the survey in Surakarta, Central Java, in 2017, many cadres did not know about stimulation detection and early interventions development (SDEID). The purpose of this study was to analyze the effect of SDEID training based on group dynamics on cadre’s motivation and skill.Subjects and Method: This study was a quasy experiment conducted in Kadipiro, Surakarta, Central Java, from February to September 2018. A sample of 21 cadres was selected for this study by total sampling. The dependent variable was motivation and skill. The independent variables were SDEID training. The data were collected by questionnaire and analyzed by paired t-test.Results: There was no difference motivation before (mean= 64.62; SD= 4.95) and after (mean= 63.62; SD= 5.17) training, but it was statistically non-significant (p= 0.526). Cadre’s skill after (mean= 29.71; SD= 6.52) was higher than before training (mean= 11.00; SD= 5.24) and it was statistically significant (p<0.001).Conclusion: SDEID training based on group dynamics is effective to improve cadre’s skill.Keywords: SDEID training, group dynamics, motivation, skill, cadresCorrespondence: Rusiana Sri Haryanti. Jl. Tulang Bawang Selatan No. 26, Kadipiro, Banjarsari, Surakarta, Central Java. Mobile: 085702162126, 082225297203. Email: triapipit20@gmail.com, rusianamolyn@gmail.com. Journal of Maternal and Child Health (2019), 4(5): 351-357https://doi.org/10.26911/thejmch.2019.04.05.08